Electrostatic Powder Coating as a Novel Process for High-Voltage Insulation Applications - Scholl, Moritz; Vogel, Nicolas; Lang, Steffen (Advanced Engineering Materials, 2023)
A novel strategy for manufacturing of the main insulation of high-voltage rotating machines is presented. The developed process is based on established electrostatic powder coating equipment. Using complete automation enables the precise and reproducible application of homogeneous powder coating layers. Individual layers can be stacked by process repetitions to achieve a desired layer thickness. This coating strategy alters the particle deposition process by introducing additional capillary bridges that significantly increase powder adhesion. A systematic parameter study is performed to provide process–structure relations connecting various process parameters with the resultant coating thickness and homogeneity. The parameters of the developed coating process are iteratively improved to maximize coating homogeneity and minimize defect density, the most critical parameters in high-voltage insulation applications. The obtained powder coatings with a target thickness of 1.5 mm are subjected to electrical testing to examine the partial discharge activity as a key criterion for a functional insulating coating. The measurements reveal no significant partial discharge activity up to an electric field strength of 10 kV mm−1, demonstrating that this novel strategy for the production of the main insulation of high-voltage rotating equipment surpasses the state-of-the-art process in terms of partial discharge activity.
CRIS-Team Scopus Importer:2023-07-28
Keywords: electrical insulation; high voltages; powder coating; process optimization